Study on the Height of Fractured Zone inside Overlying Strata under High-Intensity Mining in China - Guo Wenbing; Zhao Gaobo; Lou Gaozhong; Wang Shuren (International Conference on Ground Control in Mining, 2018)
"The height of a fractured zone due to high-intensity mining (HIM) plays a vital role in the safety analysis of coal mining under bodies of water. This paper described the characteristics of HIM. The processes of overburden failure transfer (OFT) are analyzed. The state of destruction transfers from a certain stratum to the upper stratum as face advance distance increases, and the processes of OFT are divided into two stages: transmission development stage and transmission termination stage. Through theoretical analysis, the limited suspension-distance and limited overhanging distance of each stratum are proposed to judge the damage of each layer. Based on this, the OFT criteria of fractured zone development are obtained. The mechanical model of strata suspended integrity and overhanging stability are established. Finally, a new method to predict the height of fractured zone due to HIM is put forward based on the processes of OFT, the limited suspension-distance, and the limited overhanging distance. Further, a HIM panel in the Datong coal mine is taken as an example. Theoretical methods are proposed, and engineering analogy is used to predict the height of the fractured zone, which is compared with in-situ measurements reported in the literature. The results show that the in-situ measurements for the height of the fractured zone are in close agreement with the theoretical calculation result. Therefore, the rationality and reliability of the theoretical method proposed to predict the height of fractured zone is verified.INTRODUCTIONThe height of the fractured zone (HFZ) due to the exploitation of coal is a key parameter for the safety analysis of coal mining under a body of water (Wenbing, Youfeng, and Hou, 2012). Accordingly, it is necessary to predict HFZ under the corresponding mining conditions before coal mining."